The Time‐resolved and Extreme‐conditions XAS (TEXAS) facility at the European Synchrotron Radiation Facility: the energy‐dispersive X‐ray absorption spectroscopy beamline ID24. (1st January 2016) - Pascarelli, S.; Mathon, O.; Mairs, T.; Kantor, I.; Agostini, G.; Strohm, C.; Pasternak, S.; Perrin, F.; Berruyer, G.; Chappelet, P.; Clavel, C.; Dominguez, M. C.
Abstract : The European Synchrotron Radiation Facility has recently made available to the user community a facility totally dedicated to Time‐resolved and Extreme‐conditions X‐ray Absorption Spectroscopy – TEXAS. Based on an upgrade of the former energy‐dispersive XAS beamline ID24, it provides a unique experimental tool combining unprecedented brilliance (up to 10 14 photons s −1 on a 4 µm × 4 µm FWHM spot) and detection speed for a full EXAFS spectrum (100 ps per spectrum). The science mission includes studies of processes down to the nanosecond timescale, and investigations of matter at extreme pressure (500 GPa), temperature (10000 K) and magnetic field (30 T). The core activities of the beamline are centered on new experiments dedicated to the investigation of extreme states of matter that can be maintained only for very short periods of time. Here the infrastructure, optical scheme, detection systems and sample environments used to enable the mission‐critical performance are described, and examples of first results on the investigation of the electronic and local structure in melts at pressure and temperature conditions relevant to the Earth's interior and in laser‐shocked matter are given.